Hubungan Kepemimpinan dengan Perilaku Individu dalam Organisasi - Shalahuddin Shalahuddin; Akmaluddin Akmaluddin; Muhammad Fadli (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
A leader's ability to inspire followers to take action is a major component in the success or failure of any given company. Examining how leadership in companies affects both individual behavior and organizational performance is the primary goal of this research. Reviewing a number of scholarly journals and other relevant literature sources is the basis of this library research strategy. An organization's morale, discipline, and performance may all benefit from a change in leadership style, according to the findings. Factors both internal and external to the individual, such as their motivation and personality, as well as their work environment and corporate culture, significantly influence employee behavior. Effective leadership plays a crucial role in directing these factors toward positive outcomes by fostering employee engagement, commitment, and productivity. Furthermore, leaders who communicate clearly, provide support, and demonstrate integrity are more likely to gain the trust and cooperation of their subordinates. The study also highlights that different organizational contexts may require different leadership approaches to achieve optimal results. As a result of good leadership, people will act in a way that helps the company reach its objectives. Thus, it is essential for leaders to have an understanding of personal traits and develop leadership styles that are suitable for the specific circumstances inside their organizations, thereby enhancing both individual and organizational success in the long term.